1992
DOI: 10.1163/156856292x00213
|View full text |Cite
|
Sign up to set email alerts
|

Growth of uropathogenic Escherichia coli strains at solid surfaces

Abstract: The adhesion and growth of two catheter-associated (O2K2 and O83K?) and two non catheter-associated (O111K58 and O157K-) uropathogenic Escherichia coli strains on glass, poly(methyl methacrylate) (PMMA), a negatively charged copolymer of MMA and methacrylic acid (MAA) and a positively charged copolymer of MMA and trimethylaminoethyl methacrylate chloride (TMAEMA-Cl) were studied. The solid surfaces were placed in a parallel plate perfusion system. After preadhesion of the bacteria onto the surfaces, growth was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 34 publications
2
14
0
1
Order By: Relevance
“…A positive correlation between substratum hydrophobicity and the detachment of adherent biofilm was established by other studies. According to this approach, bacteria attached to hydrophobic materials were more easily removed from them (Harkes et al, 1992; Reid et al, 1993; Eginton et al, 1995; Bos et al, 2000; Gómez-Suárez et al, 2001). On the other hand, S. aureus found to attach more effectively on stainless steel surfaces in comparison with glass ones, while organosilanes enhance the adherence of bacterium to modified glass surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…A positive correlation between substratum hydrophobicity and the detachment of adherent biofilm was established by other studies. According to this approach, bacteria attached to hydrophobic materials were more easily removed from them (Harkes et al, 1992; Reid et al, 1993; Eginton et al, 1995; Bos et al, 2000; Gómez-Suárez et al, 2001). On the other hand, S. aureus found to attach more effectively on stainless steel surfaces in comparison with glass ones, while organosilanes enhance the adherence of bacterium to modified glass surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a variety of virulence factors in E. coli , such as hemolysin, fimbriae, lipopolysaccharide (LPS), secreted proteins, capsules and iron-acquisition systems [11], [12], which allow bacterial colonization in the mucosal epithelial cells lining the urogenital tract, invade, and further form intracellular biofilm-like pods in uroepithelial cells [13]. Remarkably, UPEC is capable of forming biofilms on the abiotic surfaces of indwelling medical devices such as catheters [14], [15], which lead to “Catheter-Associated Urinary Tract Infection” (CAUTI) in clinics [16]. CAUTI is especially fatal in immunocompromised, debilitated and diabetic patients [17], [18].…”
Section: Introductionmentioning
confidence: 99%
“…have reported that the use of cationic aluminium ions affected the surface negativity of the root cell membranes, which resulted in the destabilization of the membranes. Harkes et al . witnessed the absence of growth of microorganisms (E. coli) on the positively charged poly(methylmethacrylate) films.…”
Section: Resultsmentioning
confidence: 99%